Women`s Empowerment through Non-Formal Education Programs to Increase Women’s Confidence and Self-Potential - Zaetun, Asih; Yusuf, Amin; Arbarini, Mintarsih; Siswanto, Yudi; Mikeladze, Tamar (Journal of Nonformal Education, 2026)
Background: Women’s empowerment is an important component of sustainable development. However, gender inequality remains evident in Indonesia’s agricultural sector. Although women account for about 36.7% of the agricultural workforce, their contributions are often viewed only as supporting roles rather than as primary actors. Women Farmers Groups (WFG) have emerged as grassroots organizations that promote women’s empowerment through non-formal education programs, including skills development, entrepreneurship training, financial literacy, and awareness of women’s rights. Research Urgency: Previous studies on WFG empowerment mainly emphasize economic outcomes, while psychological empowerment such as self-confidence and personal potential development has received limited attention. Understanding these aspects is important to strengthen women’s participation and independence in rural communities. Research Objectives: This study aims to analyze the empowerment process through non-formal education programs in WFG, focusing on strengthening women’s self-confidence and personal potential, as well as identifying supporting and inhibiting factors. Research Method: This study employed a qualitative case study approach with data were collected through interviews with six informants, observations, and documentation analysis. Data analysis used Miles and Huberman’s interactive model combined with Longwe’s gender empowerment framework. Research Findings: The findings show that empowerment occurs through four stages: awareness building, capacity development, participation, and self-reliance. Non-formal education programs such as skills training, life skills education, entrepreneurship training, and literacy activities significantly increased members’ confidence and potential. Internal support from leadership and member commitment, along with external institutional support, strengthened the empowerment process despite challenges related to time limitations and diverse member capacities. Research Conclusion: Non-formal education within women farmers groups provides an effective approach to strengthening women’s psychological and social empowerment in rural agricultural communities. Research Novelty: This study highlights psychological empowerment through non-formal education within women farmers groups, a dimension rarely explored in previous research that mainly focused on economic outcomes.